(3GdeDSSGJ GdUZjQI h GdeJhSWI h eTcdGJ JehjdgGs - (3QGHM(B, (3Nhfjs; (3MSGfj QbjI(B, s ((3GdbGgQI(B:s (3GjJQGc ddfTQ(B,s, 2008)
(3dbO gjef NjGQ GdJhLg fMh EfTGA GdeDSSGJ GdcHjQI daJQI WhjdI ef GdRef Ydi GdacQ GdGbJUGOi , hbO cGf gPG GdJaVjd fGHYkG ef bfGYI bOQI gPG GdfhY ef GdeTGQjY Ydi JhajQ bGYOg UfGYjI hHfjI JMJjI hQcjRI ddJfejI GdGbJUGOjI hGdGLJeGYjI , ZjQ Cf GdJZjQGJ GdcHjQI hGdcKjQI GdJi MedJgG fgGjI GdbQf GdYTQjf ZjQJ GdGJLGg fMh JaVjd hJTLjY EfTGA hbjGe GdeDSSGJ GdUZjQg hGdeJhSWI MJi CUHMJ gPg GdCNjQI ejRI eNJda GbJUGOjGJ Ohd GdYGde NGUI GdeJbOe efg , hCHQR eKGd Ydi Pdc GdGbJUGO GdjGHGfis
Keywords: (3GdJehjds; (3GdeDSSIs